Modelling the phase and chemical equilibria of aqueous solutions of alkanolamines and carbon dioxide using the SAFT-γ SW group contribution approach - Chremos,A; Forte,E; Papaioannou,V; Galindo,A; Jackson,G; Adjiman,CS (Fluid Phase Equilibria, 2015)
The speciation reactions that take place in mixtures of water, carbon dioxide (CO2), and alka-nolamines make the modelling of the chemical and uid-phase equilibria of these systems chal-lenging. We demonstrate for the rst time that the statistical associating uid theory (SAFT),formulated within a group-contribution (GC) framework based on transferable intermolecularsquare-well (SW) potentials (SAFT- SW) can be used to model successfully such complexreacting systems. The chemical reactions in these mixtures are described via a physical associ-ation model. The concept of second-order groups is introduced in the SAFT- SW approach inorder to deal with the multifunctional nature of the alkanolamines. In developing the models,several compounds including ethylamine, propylamine, ethanol, propanol, 2-aminoethanol and3-amino-1-propanol are considered. We present calculations and predictions of the uid-phasebehaviour of these compounds and a number of their aqueous mixtures with and without CO2.The group-contribution nature of the models can be used to predict the absorption of carbondioxide in aqueous solutions of 5-amino-1-pentanol and 6-amino-1-hexanol. The proposed pre-dictive approach offers a robust platform for the identi cation of new solvents and mixturesthat are viable candidates for CO2 absorption, thereby guiding experimental studies.